Effect of Radix Polygalae extract on the colonic dysfunction in rats induced by chronic restraint stress. (10th August 2022) - Li, Chen-Chen; Ye, Fan; Xu, Chen-Xi; Chang, Qi; Liu, Xin-Min; Pan, Rui-Le
Abstract: Ethnopharmacological relevance: Radix Polygalae, a commonly used traditional Chinese herb, has conventionally functioned in tranquilization and sedation, where anti-inflammation may be the underlying mechanism. Aim of the study : Chronic restraint stress (CRS), a risk factor for the etiology of intestinal disorders, was used in the present study to examine whether Radix Polygalae extract (RPE) could modulate colonic dysfunction in CRS rats. Materials and methods: Wistar rats were exposed to 28-day CRS (6 h daily), and RPE (135 mg/kg and 270 mg/kg) was intragastrically administered 1 h before CRS. Subsequently, the gut microbiota was determined using metagenomic sequencing. Colonic proinflammatory interleukin-1β, −6, and −18 were assayed using qRT–PCR and ELISA. Tight junction proteins were quantified by qRT–PCR and western blotting (WB), and tryptophan metabolic enzymes and metabolites were determined using qRT–PCR and UFLC-QTRAP-5500/MS. Moreover, protein expression of colonic tight junction proteins, NF-κB-NLRP3 signaling involved in the underlying mechanism of RPE were detected by WB. Results: RPE significantly decreased proinflammatory cytokines and reshaped the gut microbiota, especially the probiotics, including Lactobacillus and Bacteroides. Moreover, RPE could modulate the metabolite contents and enzyme expression associated with colonic tryptophan-kynurenine (TRP-KYN) metabolism and could increase tight junction protein expression in CRS rats. Furthermore, RPE inhibited the activation of NF-κB-NLRP3 signaling in the colon of CRS rats. Conclusion: RPE could modulate colonic inflammation, colonic microbiota, tight junction, TRP-KYN metabolism and NF-κB-NLRP3 signaling to reach a colonic balance of CRS rats. The present study helped us to better understand and appreciate the various beneficial effects of RPE. Graphical abstract: Image 1 Highlights: This study proved that Radix polygala could regulate intestinal dysfunction induced by CRS for the first time. Based on brain-gut communication, the sedative and tranquilizing effects of Radix Polygalae may be mediated by intestinal flora. NF-κB-NLRP3 signaling was involved in the modulating effect of RPE.